Aktivisme Sosial: Bentuk Partisipasi Masyarakat Sipil dalam Perubahan Sosial - Erfain Erfain (Journal of Humanities, Social Sciences, and Education, 2025)
Social activism is a concrete manifestation of civil society participation in driving social, political, economic, and cultural change. In both global and local contexts, social activism emerges as a response to injustice, marginalization, and the failure of the state and market to meet societal needs. This literature review aims to analyze the forms of social activism, their role in strengthening civil society, and the challenges faced in the digital era. The review shows that social activism has developed in various forms, ranging from street protests and policy advocacy to environmental movements and digital campaigns through social media. Activism is not merely mass mobilization but also a strategy for building critical awareness, solidarity, and alternative solutions to structural issues. In the digital era, social media serves as a new arena that expands the reach of activism, although it also presents challenges in the form of disinformation and movement fragmentation. This article concludes that social activism is a crucial instrument in strengthening civil society and democracy, although its effectiveness is heavily influenced by the political context, technology, and the capacity of civil society organizations themselves. Therefore, understanding social activism is key to understanding the dynamics of contemporary social change and formulating more inclusive and sustainable participation strategies.